Coconut Waste Pyrolysis Simulation Using Aspen Plus Software - Muhammad Syukri Hasan; Widayat Widayat; Sri Widodo Agung Suedi (TECHNO: JURNAL PENELITIAN, 2023)
Currently, in the world are trying to substitute fossil energy for renewable energy. One of the renewable energy is biomass energy. Biomass is a renewable natural resource derived from biological nature. Biomass from palm shells has been successfully used by the Tembilahan PLTU as an effort to substitute coal. The results of technical evaluation and monitoring show operating parameters within normal limits. Palm shells are known to have a lower sulfur content than coal so that the emissions produced are less than coal. When viewed from the characteristics based on the analysis of proximate, ultimate and calorific value, it shows that the characteristics of biomass from coconut waste, especially coconut shells, are not significantly different from biomass from palm shells. This means that coconut shells can be considered as a renewable energy source. To improve the quality of the calorific value of biomass, a pyrolysis process is carried out to produce bio-charcoal. Modeling using Aspen Plus software has a difference average of less than 6%. Simulation results of coconut shell pyrolysis with maximum yield of bio-charcoal occurring at an operating temperature of 600°C which produces a total of 30.35% bio-charcoal, a calorific value (LHV) of 33.03 MJ/kg, and an ash content of 18.99%. While the simulation results of coconut shell pyrolysis with maximum syngas yield occurred at an operating temperature of 800°C which produced 82.43% syngas, high H2 49.67% and low CO2 2.90%.